The Politics of Secularism in Ethiopia: Repression and/or Co-option towards EOTC - Liyew, Dereje Melese (European Scientific Journal, ESJ, 2024)
Secularism in Ethiopia has not been practiced as stipulated in the 1995 Federal Democratic Republic of Ethiopia (FDRE) constitution, separation of state and religion. Instead consecutive regimes since the introduction of secularism employed a tactic of co-option and repression towards the Ethiopia Orthodox Tewahido Church (EOTC) to meet their political objectives. This paper thus tried to address the nature and manifestation of government intervention in the EOTC through either co-option and/or repression with a special emphasis on the post 2018 regime. The study argues de-facto secularism in Ethiopia is far from the essence of separation of state and religion; it is a new version of religion industriously implemented by governments to upgrade the Orthodox Church in a way that fits with the political system. The secular regimes co-opted and repressed the church conditionally at any cost of the institution through Machiavellian approach. The study also finds that the Prosperity led regime was actively involved in the internal affairs of the church; in early days through co-option in the name of reconciliation with the exile synod. And in the later days via repression; massive killing of orthodox followers, burning of churches and restriction on church’s annual ceremony the like epiphany are the manifestations.